Reduction vs. metathesis in the reactions of bismuth tribromide with a bulky lithium silanide: an experimental and theoretical study - Monakhov, Kirill; Zessin, Thomas; Linti, Gerald W. (European journal of inorganic chemistry, 2010)
On reaction of BiBr3 with Li(thf)3SiPh2tBu (1) in the corresponding ratios redox/metathesis reactions were observed, yielding dibismuthane (tBuPh2Si)4Bi2 (2) and disilylbismuth halide (tBuPh2Si)2BiBr (3). The latter is a reaction intermediate in the formation of the dark-red 2. The X-ray crystal structures of 1-3 were determined by low-temperature X-ray diffraction. The Si2Bi-BiSi2 core of 2 is in the semi-eclipsed conformation. No oligomerization of “nonthermochromic” 2 was observed. Compound 3 is a mixed substituted monomer with a pyramidal environment around the bismuth center. On the basis of quantum chemical calculations, the formation of tertiary bismuthane (tBuPh2Si)3Bi is not expected for steric reasons. According to DFT-optimized geometries of the simplified model systems n[(H3Si)2Bi]2 (n = 1-3), the closed-shell attraction between intermolecular Bi centers in the chain provides a moderate elongation of the intramolecular Bi-Bi bond in the dibismuthane unit and a shortening of the intermolecular Bi···Bi contacts. According to MP4(SDQ) computations, such oligomerization is carried out by intermolecular interaction of s lone pairs that are bound together and p-type orbitals of the Bi-Bi bonds in the bismuth chain. An increase in the number of [(H3Si)2Bi]2 molecules per chain results in a decrease in the HOMO-LUMO gap and leads to a bathochromic shift. TD-PBE0 computations suggest that the lowest energy electron transition in 2 is metal-metal charge transfer. In addition, the attractive contributions in the chain [(H3A)2Bi]2···[Bi(AH3)2]2 with silyl groups (A = Si) outweigh the repulsion of the Bi···Bi centers, whereas for the alkyl-substituted bismuth chain (A = C) the repulsive van der Waals force dominates. This fact makes the rectangle oligomerization model more preferred for n[(H3A)2Bi]2 (A = C; n = 2), while for A = Si chain formation is favored in the gas phase.
Gesehen am 03.05.2023